1994
DOI: 10.1093/oxfordjournals.humrep.a138575
|View full text |Cite
|
Sign up to set email alerts
|

The chromosome constitution of human preimplantation embryos fertilized in vitro

Abstract: The chromosome constitution of five haploid, 178 diploid and 11 triploid embryos fertilized in vitro was determined after fixation on day 2 or day 3 of development. Karyotype analysis of 178 diploid embryos revealed abnormalities in 40 (22.5%) cases: 34 (19.1%) aneuploids, four (2.2%) mosaic embryos and two (1.1%) structural anomalies were identified. The majority of aneuploid karyotypes (28/34) involved a single chromosome but six embryos had aneuploidy of two or three chromosomes. The E group was most freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(48 citation statements)
references
References 0 publications
3
42
1
Order By: Relevance
“…Mosaicism persists to the blastocyst stage as it has been described in early stage embryos (Munné et al, 1994b;Munné and Cohen, 1998;Harper et al, 1995;Jamieson et al, 1994). In our series 7/8 blastocysts are mosaics.…”
Section: Discussionsupporting
confidence: 72%
“…Mosaicism persists to the blastocyst stage as it has been described in early stage embryos (Munné et al, 1994b;Munné and Cohen, 1998;Harper et al, 1995;Jamieson et al, 1994). In our series 7/8 blastocysts are mosaics.…”
Section: Discussionsupporting
confidence: 72%
“…Oocytes ( Recently, Jamieson et al [1994] studied 178 diploid embryos fertilized in vitro and found 43 (24%) to be nonmosaic aneuploid. About half were hyperploid and half hypoploid, supporting the idea that trisomic and monosomic conceptions occur equally frequently but that monosomics are lost before implantation.…”
Section: 5mentioning
confidence: 99%
“…Studies of human embryos using FISH have shown that approximately 70% of preimplantation embryos have a mosaic aneuploidy karyotype (Harrison et al, 2000;Voullaire et al, 2000;Wells and Delhanty, 2000;Sandalinas et al, 2001;Bielanska et al, 2002). Mosaicism has also been observed by other methods such as performing karyotyping on day 2 or 3 embryos (Jamieson et al, 1994). Comparative genomic hybridization (CGH) on metaphase chromosomes offers the advantage of allowing all chromosomes to be analyzed.…”
mentioning
confidence: 99%